DEVELOPMENT OF EXPERIENTIAL LEARNING-BASED LEARNING MODULE TO IMPROVE CREATIVE THINKING ABILITY IN WRITING FREE POETRY CLASS IV OF STATE ELEMENTARY SCHOOL 166492, TEBING TINGGI CITY - Susilawati Susilawati; Wisman Hadi; Evi Eviyanti (Sensei International Journal of Education and Linguistic, 2021)
This study aims to describe the level of feasibility and effectiveness of developing experiential learning-based learning modules in improving students creative thinking skills in writing free poetry. This research was conducted at the 166492 public elementary school, Tanjung Marulak Village, Tebingtinggi City, North Sumatra Province. The subjects of this study were all fourth grade students of State Elementary School 166492 Tebingtinggi City for the 2020/2021 academic year, totaling 50 students. This research method is Borg & Gall development research. The results showed (1) Based on the results of the validity of material experts 85.42%, design experts 94.23%, and linguists 94, 44%. From the results of the validation of the developed module, the module is included in the very good criteria and is declared valid and feasible to use; (2) The experiential learning-based learning module is categorized as practical because the module resulting from the students responses from trial I and trial II has increased; and (3) Based on the research results, the experiential learning-based learning module is said to be effective in learning with the assumption that students Indonesian values are higher when using the module.